Honor, vengeance, and social trouble : pardon letters in the Burgundian Low Countries - Arnade, Peter J.; Prevenier, Walter (Ithaca : Cornell University Press, 2015)
Among the more intriguing documentary sources from late medieval Europe are pardon letters--petitions sent by those condemned for serious crimes to monarchs and princes in France and the Low Countries in the hopes of receiving a full pardon. The fifteenth-century Burgundian Low Countries and duchy of Burgundy produced a large cache of these petitions, from both major cities (Bruges, Ghent, Antwerp, and Dijon) and rural communities. In Honor, Vengeance, and Social Trouble, Peter Arnade and Walter Prevenier present the first study in English of these letters to explore and interrogate the boundaries between these sources' internal, discursive properties and the social world beyond the written text. Honor, Vengeance, and Social Trouble takes the reader out onto the streets and into the taverns, homes, and workplaces of the Burgundian territories, charting the most pressing social concerns of the day: everything from family disputes and vendettas to marital infidelity and property conflicts--and, more generally, the problems of public violence, abduction and rape, and the role of honor and revenge in adjudicating disputes. Arnade and Prevenier examine why the right to pardon was often enacted by the Burgundian dukes and how it came to compete with more traditional legal means of resolving disputes. In addition, they consider the pardon letter as a historical source, highlighting the limitations and pitfalls of relying on documents that are, by their very nature, narratives shaped by the petitioner to seek a favored outcome. The book also includes a detailed case study of a female actress turned prostitute. An example of microhistory at its best, Honor, Vengeance, and Social Trouble will challenge scholars while being accessible to students in courses on medieval and early modern Europe or on historiography.
Social discord : disputes, vendettas, and political clients -- Violence, honor, and sexuality -- Marriage conflicts and the pardon letter -- Actress, wife, or lover? : Maria van der Hoeven defamed and defended.
Includes bibliographical references (pages 231-233) and index.
Print version record.
In English.
JSTOR
Keywords: Netherlands -- History -- House of Burgundy, 1384-1477 -- Sources; Benelux countries -- History -- To 1500 -- Sources; Sociological jurisprudence -- Benelux countries -- History -- To 1500 -- Sources; Pardon -- Benelux countries -- History -- To 1500 -- Sources; Crime -- Benelux countries -- History -- To 1500 -- Sources; Pays-Bas -- Histoire -- 1384-1477 (Maison de Bourgogne) -- Sources; SOCIAL SCIENCE -- Criminology; RELIGION -- Christian Church -- History; History -- Sources; Crime; Pardon; Sociological jurisprudence; Benelux countries; Netherlands; Straftat; Gnadenrecht; Belgien; Niederlande; Luxemburg; To 1500; History; Sources